Sources of value added tax and its effects on economic growth in developing countries - Kolahi, Seyyed Hossein Ghaffarian (2017)
Today the role of economic growth for its effect on social welfare is undeniable. For this reason, the factors influencing the economic growth are taken into account by policymakers and researchers. On the other hand, the value added tax (VAT) has been considered by most of the countries due to its numerous advantages and benefits. Hence, investigating how this type of tax affects the economic growth seems to be indispensable, particularly in developing countries. This research was established to investigate the effect of VAT on economic growth and its sources in developing countries. To this end, three objectives were formulated. The first objective was to evaluate and estimate the effect of VAT on economic growth in developing countries. The second objective was to estimate the effect of VAT on the sources of economic growth including physical capital accumulation and productivity growth in developing countries. Moreover, the third objective was to evaluate the effect of VAT on the saving in developing countries. The study employed the Generalized Method of Moments (GMM) panel estimators developed for dynamic models of panel data, proposed by Arellano and Bond (1991) and Blundell and Bond, (1999) to estimate the models. The empirical results related to the first objective showed a positive significant effect of VAT on economic growth using panel data of 62 countries for the period of 2003-13, suggesting that an increase in VAT will result in higher economic growth. The empirical results related to the second objective using panel data of 62 countries for the period of 2003-13 revealed that VAT had a significant positive effect on both sources of economic growth including capital accumulation growth and productivity growth. The empirical results related to the third objective using panel data from 62 countries for the period 2003-13 showed that the variable VAT had a significant negative impact on saving, suggesting that countries with increased VAT results in lower levels of saving. Based on the results, an increase in VAT leads to an increase in economic growth but this increase in economic growth is due to an increase in tax revenues, not due to an increase in saving.